Two new species of Gisilia Kasy, 1968 (Lepidoptera, Cosmopterigidae) from Korea with first report of piercing oviscapts in Gelechioidea - Sohn, Jae-Cheon; Park, Kyu-Tek (Zootaxa, 2018)
Two new species of Gisilia Kasy, 1968, G. melanobasis n. sp. and G. tamrae n. sp., are described from Korea. Ascalenia thoracista (Meyrick, 1915) is transferred to Gisilia and compared to two Korean congeners. External and genital features of two new species and G. thoracista are illustrated. Piercing oviscapts are reported from Gelechioidea for the first time. The occurrences of oviscapts in Lepidoptera are reviewed.